"Development of Thinking Skills" Course: Teaching TRIZ in Academic Setting. (2015) - Greenberg, Sara
Abstract: The question of "How to teach TRIZ" has been the subject of much discussion and debate. Bruner[1] argued that children should be encouraged to "treat a task as a problem for which one invents an answer, rather than finding one out there in a book or on the blackboard". This statement was taken from Dehaan's[2] article, published in 2009, on "Teaching Creativity and Inventive Problem Solving in Science" (p. 174), in which Altshuller's "Theory of inventive problem solving" has not been mentioned. This demonstrates only one aspect of why teaching TRIZ in educational systems is a challenging mission. This paper describes the process and method used for developing the Development thinking skills and problem solving course in academic settings. The proposed program is a combination of a generic design and problem solving process thinking methods. The course was developed using 4 main thinking methodologies: Mayer's general problem description, Polya's algorithm for problem solving, Altshuller's Theory of inventive problem solving and System thinking. The new "Development thinking skills" course program is expected to overcome teaching and studying difficulties in acquiring advances problem solving skills in higher education setting.